HUBUNGAN DISIPLIN KERJA GURU DENGAN KINERJA GURU DALAM PROSES PEMBELAJARAN DI SDIT AT-TAQWA NAROGONG - Dina Satifah; Dariyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whether there is a relationship between teachers' work discipline and their performance in the learning process at SDIT At-Taqwa Narogong. The research employs a quantitative approach using a correlational method. The population of this study consists of all 30 teachers at the school, with a saturated sampling technique applied. The instruments used include questionnaires and documentation, both of which have been tested for validity and reliability. Data analysis techniques include descriptive analysis, prerequisite tests, and hypothesis testing. The quantitative research results indicate a positive relationship between teachers' work discipline and their performance in the learning process. The calculated correlation coefficient (r) is 0.420, which falls into the moderate category.